Adapting nurse‐led cystoscopy experience to the United States: Tele‐cystoscopy a possible compromise?. Issue 2 (26th June 2019) - Beller, Haerin; Lobo, Jennifer M.; Horton, Bethany J.; Sims, Terran; Corey, Thomas; Tyson, Teresa; Schenkman, Noah S.; Krupski, Tracey L.; Jones, Randy A.
Abstract: Urology workforce shortages in rural areas limit access to diagnostic cystoscopy for hematuria or surveillance cystoscopy for patients with bladder cancer. To address this, we developed a tele‐cystoscopy model in which urologic advanced practice professionals (APPs) perform cystoscopies that are interpreted in real‐time by board‐certified urologists at their home institution. This collaborative model allows the cystoscopic interpretation to be performed by a board‐certified urologist. This model may both improve access for patients in remote locations and may lead to greater acceptance of nurse‐led cystoscopy in the medical legal environment found in the United States.